An M(2)-like muscarinic receptor enhances a delayed rectifier K(+) current in rat sympathetic neurones - Cruzblanca, H (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Resting superior cervical ganglion (SCG) neurones are phasic cells that switch to a tonic mode of firing upon muscarinic receptor stimulation. This effect is partially due to the muscarinic inhibition of the M-current. Because delayed rectifier K(+) channels are essential to sustain tonic firing in central neurones, we asked whether the delayed rectifier current I(KV) in SCG neurones was modulated by the muscarinic receptors expressed in these cells. EXPERIMENTAL APPROACH: Whole-cell patch-clamp records of M-current and I(KV) were done in cultured or acutely dissociated rat SCG neurones. To characterize the receptor that regulates I(KV), cells were bathed with muscarinic agonists and antagonists, relatively specific for receptor subtypes. KEY RESULTS: The muscarinic agonist oxotremorine-M (Oxo-M) enhanced I(KV) by ∼46% relative to its basal value. This effect remained unaltered when M-current was suppressed by linopirdine or Ba(2+). Enhancement of I(KV) was insensitive to the M(1)-antagonist pirenzepine, whereas it was inhibited (∼60%) by the M(2/4)-antagonist himbacine. Further, the relatively specific M(2)-agonist bethanechol was as potent as Oxo-M in enhancing I(KV). The modulation of I(KV) was insensitive to pertussis toxin (PTX), but was severely attenuated when internal ATP was replaced by its non-hydrolysable analogue AMP-PNP. CONCLUSIONS AND IMPLICATIONS: These results suggest that an M(2)-like muscarinic receptor couples to a PTX-insensitive G-protein and to an ATP-dependent pathway to enhance I(KV). Modulation of I(KV) must be taken into consideration in order to understand more precisely how muscarinic receptors acting on different ion channels regulate sympathetic excitability.